The Effect of Dates Consumption On Increased Hemoglobin Levels In Third Trimester Pregnant Women At BPM “E”, Serang - Choirunissa, Risza; Widowati, Retno; Putri, Astrid Estiyana (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to determine the effect of dates consumption on increased hemoglobin levels in third trimester pregnant women at BPM “E”, Serang. This study used quasi experimental method with non-equivalent control group using a control group and experimental group. Data were collected using observation sheets of increased hemoglobin levels for 14 days. Univariate analysis showed that mean increase in hemoglobin levels in pregnant women who consumed Fe tablets was 0.3 g / dL and those who consumed dates was 1.8 g / dL. In the bivariate analysis using the paired t-test, P value of the experimental group was 0.000 (P <0.05) and independent t-test obtained P value of 0.03 (P <0.05) which can be concluded that there was an effect of dates consumption on increased hemoglobin levels in third trimester pregnant women. It is expected that pregnant women can use natural methods by consuming dates to increase hemoglobin levels